2017
DOI: 10.1038/s41598-017-12054-7
|View full text |Cite
|
Sign up to set email alerts
|

The cancer chemotherapeutic agent paclitaxel (Taxol) reduces hippocampal neurogenesis via down-regulation of vesicular zinc

Abstract: Chemotherapy-induced cognitive impairment (CICI) is increasingly recognized as a major unwanted side effect of an otherwise highly valuable life-saving technology. In part, this awareness is a result of increased cancer survival rates following chemotherapy. Altered hippocampal neurogenesis may play a role in mediating CICI. In particular, zinc could act as a key regulator of this process. To test this hypothesis, we administered paclitaxel (Px) to male C57BL/6 mice for set time periods and then evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Study 1). In another study (Lee et al, 2017), a more robust chronic paclitaxel dosing regimen (10 mg/kg every other day for 30 days) did not alter cellular proliferation in mice, as measured by Ki67 expression levels, suggesting that paclitaxel’s impact on hippocampal cellular proliferation may be dependent on many factors including age, species and treatment regimen. Beneficial effects of prior voluntary exercise on paclitaxel-induced neuropathic nociception may be more robust and pervasive than its protective effects against paclitaxel-induced deficits in hippocampal cell proliferation and survival, which, in our study, appear to require ongoing voluntary exercise…”
Section: Discussionmentioning
confidence: 98%
“…Study 1). In another study (Lee et al, 2017), a more robust chronic paclitaxel dosing regimen (10 mg/kg every other day for 30 days) did not alter cellular proliferation in mice, as measured by Ki67 expression levels, suggesting that paclitaxel’s impact on hippocampal cellular proliferation may be dependent on many factors including age, species and treatment regimen. Beneficial effects of prior voluntary exercise on paclitaxel-induced neuropathic nociception may be more robust and pervasive than its protective effects against paclitaxel-induced deficits in hippocampal cell proliferation and survival, which, in our study, appear to require ongoing voluntary exercise…”
Section: Discussionmentioning
confidence: 98%
“…In addition, cancer chemotherapy causes disruption of vesicular Zn 2+ stores in hippocampal mossy fiber terminals which leads to decrease in hippocampal neurogenesis. A recent study reported that the dietary Zn 2+ supplement can act as a simple alternative treatment for hippocampal neurogenesis to ameliorate Chemotherapy-induced cognitive impairment 14 . Hence, detection of Zn 2+ concentration and its dynamics in both physiological and pathological conditions pose high demand.…”
Section: Introductionmentioning
confidence: 99%
“…47,48) Our recent published work has suggested that reduced vesicular zinc is related to the CICI-induced reduction of neurogenesis and accompanying cognitive decline. 14) Our lab has demonstrated that zinc may be an essential element for hippocampal neurogenesis. Vesicular zinc is most highly localized in the hippocampal mossy fibers of dentate granule cells.…”
Section: Chemotherapeutic Agent Paclitaxel Re-duces Vesicular Zinc Lementioning
confidence: 99%
“…These results suggest that reduced vesicular zinc pools in hippocampal synaptic terminals by Px may interfere with neurogenesis and therefore lead to the cognitive decline seen in patients after chemotherapy. 14) Thus, we have proposed that zinc supplements can be used as a simple alternative treatment to ameliorate CICI. However, further clinical investigation in humans is needed.…”
Section: Chemotherapeutic Agent Paclitaxel Re-duces Vesicular Zinc Lementioning
confidence: 99%
See 1 more Smart Citation